ASPECTS CONCERNING THE COMPETITION OF BUSINESS OPERATORS IN THE CONTEMPORARY BUSINESS ENVIRONMENT - STEFANESCU, Ana Roxana (Annals of Spiru Haret University. Economic Series, 2018)
Abstract The competitive, ethical and legal attitude is a powerful element in increasing business development rhythm, but if it is guided towards the level of sublegal and the hits applied to competitors, then it turns into an anti-business, anti-development, anti-cohabitation, anti –productive environment. The competitive, ethical and legal environment is beneficial for economic activity and social development. Regardless of the form in which it takes place, business competition is complex in nature, including the development environment, resources, methods, contestants and competitors, directions, market shares, factors and locations. Competitive complexity includes cultural factors, behaviors, promotional policies, regularities and morality, conjectures and recessions, personnel recruitment and picking up, distribution opportunities and facilities, complex and indispensable utilities, sharing human resources, energy, financial and material resources, policies of selection, cooperation, counteraction, annihilation or removal, procurement policies, dominance in areas or market shares, ingenuity, new products and services, investments and financial availability, capabilities of organization, of presentation, demonstration, of keeping the relations with the consumers.